Iranian Efl Learners’ Listening Comprehension Of Texts Read By Instructors, Peers And Native Speakers - Serraj, Samaneh (2008)

(untitled)
This study is an attempt to gauge Iranian EFL learners’ listening comprehension of different texts read by Persian and non-Persian speaking EFL learners, Persian speaking English instructors and native English speakers. The globalization of English has witnessed an increase in the number of non-native English speakers born in different countries and those learning English in EFL contexts. These learners often learn English as a foreign language and they will never leave their countries and encounter neither other non-native English speakers nor native ones. This fact highlights the EFL learners’ problem of intelligibility and comprehensibility in other contexts. This study attempts to answer to two questions: (i) While listening to oral readings, do Iranian advanced learners perceive the English of their peers with similar L1 background or/and age to be better than that of their instructors or native English speakers?, and (ii) While listening to oral readings, do Iranian intermediate learners perceive the English of their peers with similar L1 background or/and age to be better than that of their instructors or native English speakers? The data was collected using a quantitative research method with a descriptive design and cross-sectional method. The subject of the study is a group of 64 female Iranian EFL learners (aged 18-24). They are divided into two groups of advanced and intermediate based on a placement test, and then subdivided into four subgroups based on the Latin Square. Two sets of semi direct CD mediated comprehension texts followed by multiple-choice questions were administrated. The data is analyzed using ANOVA. The findings show that for the advanced groups, the difference between aural perceptions is significant and the similarities of L1 and/or age background cause a better result in their listening comprehension tests. On the other hand, although the difference in the scores from the listening comprehension tests is significant for the intermediate groups, the similarities of L1 and/or age background did not cause a better comprehension. The advanced groups perceived their Persian-speaking peers the best, followed by their instructors, non-Persian speaking peers and finally native English speakers. The intermediate group, however, perceived native English speakers the best, followed by their instructors, their Persian-speaking peers and finally non-Persian speaking peers.